THE CONTRIBUTION OF WOMEN'S EMPLOYMENT IN TECHNOLOGY TO THE ECONOMY FOR SUSTAINABLE DEVELOPMENT: AN ECONOMETRIC ANALYSIS (Third Sector Social Economic Review, 2025)
Today, women's employment is of great importance in the country's economy and prosperity for the realization of social or individual sustainable development. When some factors that enable women to participate in economic life are taken into account, the information and communication technologies of digital change and professional development in these sectors have increased the employment rate of women. Increasing women's employment for countries is one of the main goals of sustainable growth and social development, and it progresses in proportion to this. The phenomenon of economic growth and development includes variables of social, economic and technological factors, so in this study, economic and technological variables affecting women's employment were examined for Turkey. In this study, the relationship between economic growth and women's employment is focused on Dec. In addition to women's employment, the Granger Causality analysis of GDP, which expresses economic Deciency between 2005 and 2023, and the independent variables of education and information technologies affecting the female workforce were tested. VAR (Vector Autoregressive Regression) analysis was used to examine the effect of women's employment in the field of technology on economic growth and changes in the female labor force participation rate. In addition, PP, KPSS, ADF tests were used for the stability analysis of the variables. The empirical results of the study show the existence of a Johensan Decoupling analysis (long-term relationship) between the variables. Finally, suggestions have been made to increase women's employment. The importance of the increase in women's employment in terms of Turkey's development was emphasized.
Keywords: Sustainable Development; Labor Force of Women; Participation Rate; Women's Schooling Rate In Information Technologies; Var Analysis